Impact of Employee Participation on Job Satisfaction in Nepalese Commercial Banks - Chapagai, Rishi Ram (PYC Nepal Journal of Management, 2011)
This article attempts to examine the relationship between employee participation and job satisfaction in Nepalese commercial banks for which four Nepalese commercial banks — two each from government and private sectors— were selected as the sample. Based on primary data the study adopted a questionnaire survey on 200 employees from the assistant to manager levels of the sample organizations and it received response from altogether 146 respondents (73 percent). Based on explanatory research design, the study showed that that there is positive relationship between employee participation and job satisfaction in Nepalese banks. The findings reveal that employee participation is an important determinant of job satisfaction. Increased employee participation makes a positive effect on job satisfaction of Nepalese banking employees.